eQTL and multi-omics integration reveal PPIH as a prognostic and immunotherapeutic biomarker - Lv, Fenglin; Zhang, Xinlu; Wu, Yanmei; Li, Zhipeng; Zheng, Xiaomen; Zhou, Huaxin; Wang, Wei (Frontiers in Immunology, 2025)
BackgroundMalignant tumors remain a major threat to global human health. This study aimed to systematically integrate multi-omics data to identify a candidate gene with biomarker potential across diverse cancer types and to evaluate its possible clinical applications in oncology.MethodsWe first performed Mendelian randomization based on summary statistics to integrate blood expression quantitative trait loci data with genome-wide association study results from esophageal adenocarcinoma, stomach cancer, and clear cell renal cell carcinoma. A comprehensive series of multi-omics bioinformatics analyses was subsequently conducted to assess the gene’s expression patterns, genomic alterations, prognostic relevance, and associations with the tumor microenvironment (TME) across various cancer types. In addition, single-cell transcriptome data were analyzed to explore the gene’s functional roles in the TME. The key findings were further validated through in vitro experiments.ResultsMendelian randomization identified peptidylprolyl isomerase H (PPIH) as a potential biomarker across multiple malignancies. Single-cell transcriptome analysis suggested that this gene may enhance the proliferative ability of malignant cells and participate in communication between immune and stromal components in the TME. Multi-omics analyses revealed that the gene is abnormally expressed and significantly correlated with patient prognosis in several cancer types. Consistently, in vitro assays demonstrated that increased expression of PPIH promotes the proliferation, migration, and invasion of hepatocellular carcinoma (HCC) cells.ConclusionThis study highlights PPIH as a candidate biomarker with pan-cancer relevance and potential clinical value. These findings offer new directions for cancer diagnosis and provide a foundation for further development of targeted therapeutic approaches.